Normal Aging of the Human Brain Potentiates the Neuropathologies of Parkinson's Disease, Depression, and Alzheimer's Disease: Behavioural Implications - Beck, Charles H. M. (Canadian Journal of Counselling and Psychotherapy, 2012)
The normal aging process of the human brain involves neuropathological changes which potentiate the progress of Parkinson's disease, depression and Alzheimer's disease. Thus the old person is not just a younger person afflicted with an especially stressful array of environmental contingencies. The professional should be prepared for the insidious development of milder forms of the symptoms of these diseases, in normal aging persons. As a corollary Parkinsonism, depression and Alzheimer's disease may be viewed as anacceleration of normal aging.